RET, NTRK, ALK, BRAF, and MET Fusions in a Large Cohort of Pediatric Papillary Thyroid Carcinomas - Peková Bulanová, Barbora; Sykorova, Vlasta; Dvorakova, Sarka; Vaclavikova, Eliska; Moravcova, Jitka; Katra, Rami; Astl, Jaromir; Vlcek, Petr; Nováková Kodetová, Daniela; Vcelak, Josef; Bendlova, Bela (Thyroid, 2020)
Background: Pediatric papillary thyroid carcinoma (PTC) is a rare malignancy, but with increasing incidence. Pediatric PTCs have distinct clinical and pathological features and even the molecular profile differs from adult PTCs. Somatic point mutations in pediatric PTCs have been previously described and studied, but complex information about fusion genes is lacking. The aim of this study was to identify different fusion genes in a large cohort of pediatric PTCs and to correlate them with clinical and pathological data of patients. Methods: The cohort consisted of 93 pediatric PTC patients (6-20 years old). DNA and RNA were extracted from fresh frozen tissue samples, followed by DNA and RNA-targeted next-generation sequencing analyses. Fusion gene-positive samples were verified by real-time polymerase chain reaction. Results: A genetic alteration was found in 72/93 (77.4%) pediatric PTC cases. In 52/93 (55.9%) pediatric PTC patients, a fusion gene was detected. Twenty different types of RET, NTRK3, ALK, NTRK1, BRAF, and MET fusions were found, of which five novel, TPR/RET, IKBKG/RET, BBIP1/RET, OPTN/BRAF, and EML4/MET, rearrangements were identified and a CUL1/BRAF rearrangement that has not been previously described in thyroid cancer. Fusion gene-positive PTCs were significantly associated with the mixture of classical and follicular variants of PTC, extrathyroidal extension, higher T classification, lymph node and distant metastases, chronic lymphocytic thyroiditis, and frequent occurrence of psammoma bodies compared with fusion gene-negative PTCs. Fusion-positive patients also received more doses of radioiodine therapy. The most common fusion genes were the RET fusions, followed by NTRK3 fusions. RET fusions were associated with more frequent lymph node and distant metastases and psammoma bodies, and NTRK3 fusions were associated with the follicular variant of PTC. Conclusions: Fusion genes were the most common genetic alterations in pediatric PTCs. Fusion gene-positive PTCs were associated with more aggressive disease than fusion gene-negative PTCs.
Keywords: Gene Fusion; Proto-Oncogene Proteins c-ret; Receptor, trkC; Humans; papilární karcinom štítné žlázy; dítě; Proto-Oncogene Proteins B-raf; Biomarkers, Tumor; Child; Proto-Oncogene Proteins c-met; protoonkogenní proteiny c-ret; Female; mladý dospělý; věkové faktory; Phenotype; Thyroid Neoplasms; lidé; Thyroid Cancer, Papillary; nádorové biomarkery; protoonkogenní proteiny B-raf; ženské pohlaví; bodová mutace; Male; fenotyp; Adolescent; prognóza; genetická predispozice k nemoci; Genetic Predisposition to Disease; protoonkogenní proteiny c-met; receptor trkC; Point Mutation; Gene Rearrangement; Young Adult; nádory štítné žlázy; genová přestavba; Age Factors; fúze genů; Receptor, trkA; receptor trkA; mužské pohlaví; Prognosis; mladiství